2023
DOI: 10.3390/v15061325
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Potency and Safety of Live-Attenuated Peste des Petits Ruminant Virus Vaccine in Goats by Detection of Cellular and Humoral Immune Response

Abstract: The peste des petits ruminant (PPR) virus is a transboundary virus found in small domestic ruminants that causes high morbidity and mortality in naive herds. PPR can be effectively controlled and eradicated by vaccinating small domestic ruminants with a live-attenuated peste des petits ruminant virus (PPRV) vaccine, which provides long-lasting immunity. We studied the potency and safety of a live-attenuated vaccine in goats by detecting their cellular and humoral immune responses. Six goats were subcutaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…It is not possible to say from the study presented here whether the absence of live excreted virus was due to the pre-neutralisation of virus particles by circulating anti-H antibody, or to an absence of whole virus particles, with the detected viral RNA reflecting cell debris from infected cells. There is probably a minimum level of virus that must be circulating in infected animals in order for live virus to be excreted: a recent study 38 using modern RT-qPCR detection methods have detected viral RNA in blood and swabs of animals following vaccination with the live attenuated Nigeria/75 vaccine strain of PPRV, at similar levels to that found in this study in single-vaccinated animals following challenge, even though the live attenuated PPRV vaccine strain has never been reported as being excreted.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to say from the study presented here whether the absence of live excreted virus was due to the pre-neutralisation of virus particles by circulating anti-H antibody, or to an absence of whole virus particles, with the detected viral RNA reflecting cell debris from infected cells. There is probably a minimum level of virus that must be circulating in infected animals in order for live virus to be excreted: a recent study 38 using modern RT-qPCR detection methods have detected viral RNA in blood and swabs of animals following vaccination with the live attenuated Nigeria/75 vaccine strain of PPRV, at similar levels to that found in this study in single-vaccinated animals following challenge, even though the live attenuated PPRV vaccine strain has never been reported as being excreted.…”
Section: Discussionmentioning
confidence: 99%
“…The N-speci c antibodies detected by the employed cELISA are not neutralizing antibodies. Nonetheless, they are considered indicators of an ongoing T-cell mediated immune response [53]. Evaluation of antibody responses following PPR vaccination using virus neutralization test (VNT), Hantigen-speci c antibodies cELISA which are neutralizing antibodies [55] or N-antigen-speci c antibodies cELISA and challenge studies reported no discrepancy between sero-conversion and protection [51; 52; 53].…”
Section: Discussionmentioning
confidence: 99%